Pengaruh Persepsi Label Halal Terhadap Keputusan Pembelian Produk Wardah Pada Masyarakat Desa Gandu - Purwanti, Neli; Aulia, Tyara (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2023)
Wardah is the originator of the trend for halal cosmetics in Indonesia. Wardah always carries a "halal" strategy in its advertising and marketing, so that Wardah is the most well-known halal cosmetic product in the community, because "halal" has become a separate brand image for Wardah. This study aims to determine the effect of perceptions of the halal label on purchasing decisions for Wardah products in the people of Gandu Village.The method used in this research is a quantitative method. Test techniques and data analysis include validity test, reliability test, percentage data description test, normality test, simple linear regression, Pearson correlation, t test and coefficient of determination (r2) using SPSS version 22.The results showed that the value of r2 was 0.293 which implies that the influence of the perceived halal label variable (X) on the purchase decision variable (Y) was 29.3% and the remaining 70.7% was influenced by other variables. The results of hypothesis testing using simple linear regression analysis show that perceptions of halal labels have a significant effect on purchasing decisions.The conclusion of the research results shows that the variable perception of the halal label and the purchase decision has a unidirectional relationship (b = 0.647), the level of closeness is moderate (r = 0.541), and the variable perception of the halal label contributes to the purchase decision variable by 29.3% with low criteria. Furthermore, based on the results of hypothesis testing (t test), it shows that the hypothesis (H1) is accepted, meaning that the perception variable of the halal label influences the purchasing decision variable.